Energetyczne uwarunkowania endogenicznego wzrostu gospodarczego - Dokturno, Zbigniew (Energy Aspects of Endogenous Economic Growth, 2009)
The paper presents energy as a physical production factor using neoclassical production function in the original model of endogenous economic growth with energy as an endogenous factor. Therefore, the paper presents a correlation between steady-state economic growth and the energy growth in the economy. The division of energy into two categories: production energy and consumption energy, leads to the possibility of economic growth based on final energy production. So the energy can be the source of added value in the energy-saving economy. The paper also presents different aspects of green energy problems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 21-30